Single-shot observation of optical rogue waves in integrable turbulence using time microscopy - Pierre Suret (Nature Portfolio, 2016)
A rogue wave is an unexpected oscillation of large amplitude and is an example of the spontaneous formation of a coherent structure out of disorder. Here, the authors develop an experimental strategy that can provide snapshots in time and thus record the real shape of optical rogue waves emerging from random noise.